THE CORPORATE INFORMATION SYSTEM OF LOGISTICS MANAGEMENT - I. V. Shatokhin (Informatika, 2017)
The corporate information system of logistics management is discussed. Its main tasks and functions are described. The system is operated in several enterprises.